PENGGUNAAN KONJUNGSI DALAM SURAT KABAR KOMPAS - Siti Qomariyah; Mangatur Sinaga; Charlina ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT: This study describe the use of conjunctions in the Kompas newspaper. The purpose of study is to examine conjunctions used, the percentage of accuracy of conjunctions, and the meaning of conjunctions used in the Kompas newspapers. This study is use qualitative research methods with a descriptive approach. Data source of this research is the headlines in the Kompas newspaper published on 20 October 2013 to 19 October 2013, as many as 115 news. Authors just take 57 news for the research sample. The results of this study refers to the problem and research purpose. First, based on the analysis found that the conjunctions used are coordinate, subordinate, correlative, between sentences, and between paragraphs. Second, the percentage of accuracy use of conjunctions in the Kompas newspaper amounting 88.6%. The percentage means that use of conjunctions in the Kompas newspaper have good. Third, the meaning of conjunctions which are in the headlines totaled to 18 are addition, consecutive, choice, opposition, the more, the time, comparison, cause, effect, requirement, expectations/goals, enlighten, content, manner, tool, utility, marker examples, and equate.Keys words: conjunction, coordinate, subordinate, correlative.